Промышленные взрывы и сейсмичность Украинского щита - Кутас, В.В.; Андрущенко, Ю.А.; Калитова, И.А. (Геофизический журнал, 2014)
Results of analysis of records and spectrograms of seismic events, registered in the Ukrainian Shield during 2009—2013 — industrial explosions in the open pits and mines and local earthquakes have been described. The values of seismic energy during earthquakes and explosions have been compared, locations of epicenters of local earthquakes have been considered taking into account tectonics of the USh.